Pembentukan “Kampung Edukasi Jaan” Sebagai Media Pelestarian Permainan Tradisional - Hena Elizabet; Lia Nirawati (BADAN PENERBIT STIEPARI PRESS, 2023)
Tourism is a trip undertaken by a group of people who visit certain places for recreational purposes, or to study the uniqueness of the tourist attractions visited in a temporary period. Jaan Village is one of the villages in Gondang District, which has beautiful and peaceful environmental conditions. Most young children in Jaan Village like to do healthy walks in the morning, especially during school holidays, they also like to play together. In Jaan Village itself, there are no tourist attractions or rides for children to play. So, after direct observation of KKNT MBKM students from UPN